Islamic Communication Ethics in Gus Kautsar’s Sermon on the Sound Horeg : Etika Komunikasi Islam dalam Ceramah Gus Kautsar tentang Sound Horeg - Faiqotul Isma Dwi Utami; Dea Fatra Nur Laili (UIN Antasari Banjarmasin, 2025)
The Sound Horeg phenomenon in East Java has become a social issue that has sparked debates regarding ethics, health, and religious values. This study analyzes the application of Islamic communication ethics in Gus Kautsar's YouTube lectures discussing this phenomenon. Using qualitative methods with content analysis, data were collected from lecture transcripts and analyzed based on six principles of Islamic communication ethics. The research sample was purposively selected from relevant videos of at least 10 minutes in length. The findings indicate that most of the principles of Islamic communication, such as sadidan, ma'rufan, balighan, maysuran, and kariman, are fulfilled, although the principles of layyina are less consistent due to the use of sarcastic humor that can trigger negative perceptions. Gus Kautsar's approach, which combines religious evidence, simple language, local humor, and social criticism, has proven effective in contextually packaging Islamic preaching messages. The contribution of this study lies in enriching the digital Islamic preaching literature, particularly in responding to controversial popular culture with a persuasive approach based on local wisdom. These results are important for developing adaptive, relevant Islamic preaching strategies that remain grounded in Islamic ethical principles to maintain social harmony amidst contemporary cultural dynamics. KEYWORDS: communication ethics; da'wah; Sound Horeg.